A Sociocultural Examination of Religiosity's Role in Coupon Proneness - Ding, William; Sprott, David; Joireman, Jeff (Psychology and Marketing, 2026)
Keywords: Consumer behaviour; Coupon; Face (sociological concept); Religiosity; Revenue; Sociocultural evolution; Survey data collection; benevolent inference; coupon proneness; dept.mrk; mixed method; religiosity; sociocultural variables

Beyond algorithm aversion: The impact of psychological readiness on algorithmic advice - Kim, H. (Computers in Human Behavior, 2025)
Keywords: Advice (programming); Advice-taking; Algorithm appreciation; Algorithm aversion; Matching (statistics); Mindset; Openness to experience; Psychological readiness; Trust; Uncertainty; dept.mrk

A systematic investigation of why P2P services are rated higher than traditional services - Unnava, Vasu; Singh, Amit Surendra; Unnava, H. Rao (Journal of Business Research, 2025)
Prior literature has reported a tendency for consumers to rate peer-to-peer (P2P) services more positively than the same services provided by traditional businesses (e.g. Airbnb vs. hotel). We first show that consumers experience greater empathy toward a P2P service provider (a person) than a traditional service provider (a business). We then show that P2P services enjoy higher evaluations because empathy for the provider leads consumers to tolerate minor negative elements in those settings as compared to traditional business settings. Further, we show that this effect is moderated by the perceived size of the business. The implications of this type of rating bias on traditional businesses and consumer welfare, and the limitations of this research, are discussed. © 2025 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: Online-reviews; Peer-to-peer; Rating-bias; Willingness-to-tolerate; dept.mrk

Are charitable gifts truly appreciated by the recipients who requested them? Impact of gift type and amount on recipients’ appreciation - Kang, In-Hye; Kim, Hyoseok (Journal of Business Research, 2025)
• For requested gifts during rite-of-passage occasions, appreciation for charitable vs. recipient-benefiting gifts depends on gift amount. • For low gift amounts, recipients appreciate charitable gifts more than recipient-benefiting gifts. • For moderate to high gift amounts, appreciation is similar between charitable and recipient-benefiting gifts. • In distant (vs. close) giver-recipient relationships, the effect of gift type on appreciation for low amounts is attenuated. • When gifts are not requested, recipients appreciate charitable gifts less than recipient-benefiting gifts. Requests for charitable cash gifts during rite-of-passage occasions (e.g., weddings) are becoming increasingly common. This research examines whether recipients’ appreciation differs depending on whether a requested cash gift is charitable (e.g., donating to support people in need) or recipient-benefiting (e.g., renovating the recipient’s kitchen). Across five studies, we find that the effect of the gift type on appreciation is moderated by the gift amount. For low amounts, recipients appreciate charitable gifts more than recipient-benefiting gifts. However, for moderate and high amounts, appreciation is similar across gift types. This effect is mediated by the recipients’ perception of whether the gift amount meets their expectations and their subsequent perception of thoughtfulness. Consistent with our mechanism, in distant giver-recipient relationships, the effect of the gift type on appreciation for low amounts is attenuated. When gifts are not requested, recipients appreciate charitable gifts less than recipient-benefiting gifts.
Keywords: Advertising; Business; Charitable gifts; Charitable giving; Conflict of interest; Donation; Economic growth; Economics; Finance; Gift appreciation; Gift giving; Gift price; Gift-giving; Marketing; Psychology; Social psychology; dept.mrk; peer-reviewed

Moral Disengagement, Machiavellianism and Academic Dishonesty - Prince, Melvin; Wang, J.; Priporas, Constantinos‐Vasilios (Journal of Academic Ethics, 2025)
Keywords: Academic Dishonesty; Academic dishonesty; Big Five personality traits; Cheating; Deviance; Dishonesty; Educational Research; Machiavellianism; Machiavellianism, Social Cognitive Theory; Moral Development; Moral Disengagement; Moral Philosophy and Applied Ethics; Moral Psychology; Moral disengagement; Morality; Personality; Psychology; Social psychology; Students; dept.mrk; peer-reviewed

Sensemaking and sustainability: a sensemaking perspective on the ethical use of big data in marketing strategizing - Wang, Emma (Junhong); Berthon, Pierre; Su, Yiran (Sustainable Development Seen Through the Lenses of Ethnoeconomics and the Circular Economy, 2024)
Despite the ethical concerns over the datafication and surveillance of individuals and groups, companies are making ever greater investments in big data. The assumptions underpinning this movement are: (1) organizations are passive implementers of big data—more data is the inevitable consequence of technology and a competitive necessity for business, (2) more data offers a more objective and accurate picture of reality and (3) more data enables better prediction. We argue that this perspective is strategically unsustainable and abdicates ethical responsibility.
Keywords: Big Data; Organization; Sensemaking; Strategizing; Sustainability; dept.mrk

Managerial Talent and Corporate Social Responsibility (CSR): How Do Talented Managers View Corporate Social Responsibility? - Chatjuthamard, Pattanaporn; Jiraporn, Pornsit; Tong, Shenghui; Singh, Manohar (International Review of Finance, 2016)
Motivated by the ongoing debate on the costs and benefits of corporate social responsibility (CSR), we explore how talented managers view CSR investments. Based on nearly 20,000 observations across 17 years, our evidence reveals a nonmonotonic effect of managerial talent on CSR. Exploiting a novel measure of managerial ability, we find that talented managers view CSR investments favorably. However, only those with especially strong talent are in favor of CSR investments. For executives ranked above the 75th percentile in terms of managerial talent, an increase in managerial ability leads to more CSR investments, suggesting that these strongly talented managers perceive CSR as enhancing firm performance. In contrast, for those with weaker talent, CSR investments are negatively associated with managerial ability, implying that these weakly talented managers view CSR as a wasteful deployment of resources. Further evidence shows that our conclusion is unlikely confounded by endogeneity.
Keywords: G30; G32; M14; dept.mrk

Is there an optimally diversified conglomerate? Gleaning answers from capital markets - Nejadmalayeri, Ali; Iyer, Subramanian Rama; Singh, Manohar (Review of Quantitative Finance and Accounting, 2017)
Motivated by recent productivity-based theories of diversification, we argue that only conglomerates with an optimal degree of diversification can utilize their comparative advantages across various industries and achieve economies of scope by eliminating redundancies. Evidence from both corporate bond and equity markets suggests that optimally diversified conglomerates consist of either (1) approximately five equally weighted divisions, or (2) one large core business segment that roughly accounts for 75 % sales. Moreover, the relative size of divisions has a critical impact on how diversification affects credit spreads and excess values. Nonparity among divisions correlates with greater costs that increase with the number of divisions.
Keywords: Conglomerates; Credit spreads; Equity discount; G10; G11; G12; Optimal diversification; dept.mrk

Shopper Search in Response to Conditional Promotions: A Function of Basket Sizes and Incentive Types - Kulkarni, Atul; Yuan, Hong (Psychology and Marketing, 2025)
Keywords: Advertising; Business; Computer science; Consumer Attitudes; Consumer Behavior; Economics; Function (biology); Incentive; Incentives; Mathematics; Microeconomics; Shopping; dept.mrk; peer-reviewed

Induction of Construal-Level Mindset via Experience of Surprise: An Abstract: Proceedings of the 2018 Academy of Marketing Science (AMS) Annual Conference | Request PDF - Kulkarni, Atul A.; Vanhamme, Joelle (2018)
Request PDF | Induction of Construal-Level Mindset via Experience of Surprise: An Abstract: Proceedings of the 2018 Academy of Marketing Science (AMS) Annual Conference | An experience of surprise is often an outcome of disconfirmation of expectations and can be associated with positive or negative affect depending... | Find, read and cite all the research you need on ResearchGate
Keywords: dept.mrk

Construal-level Mindsets Enhance Behavioral Persistence in Response to Incentive Valence - Kulkarni, Atul A.; Yuan, Hong (Journal of Behavioral Decision Making, 2017)
In this research, we find that incentive valence and construal-level mindsets can interact to influence behavioral persistence on challenging tasks. An abstract mindset improves persistence in response to positively framed incentives whereas a concrete mindset improves persistence in response to negatively framed incentives. This interaction effect can be observed even when the cues inducing construal-level mindsets are not related to the incentives or the incentivized tasks. Participants in our studies were either positively or negatively incentivized to solve a set of difficult anagrams, and were primed with an abstract or a concrete mindset using spatial (Study 1) and social (Study 2) cues. The participants persisted longer in response to the positively framed incentive when primed with spatially or socially remote cues. In contrast, for the negatively framed incentive, participants persisted longer when primed with spatially or socially proximal cues. Copyright © 2017 John Wiley & Sons, Ltd.
Keywords: construal-level; dept.mrk; incentive valence; mindset; persistence

The impact of generative AI on syllabus design and learning - Kim, Hyoseok; Koo, Thomas K. B. (Journal of Marketing Education, 2024)
This research examines the impact of generative artificial intelligence (AI) on the perception of educational content quality, specifically by comparing AI-generated and human-generated course syllabi in marketing education. Results from four studies indicate a general preference for AI-generated syllabi, attributed to their greater perceived objectivity. This preference is more pronounced in conventional courses but diminishes in unconventional ones, suggesting that the unique aspects of these courses may reduce the advantages of generative AI. In addition, disclosing the AI authorship of syllabi significantly affects their perceived quality negatively, underscoring the impact of transparency on the acceptance of AI-generated educational materials. These findings highlight the potential of generative AI in educational content creation and its limitations in certain contexts. They offer valuable insights for enhancing educational practices and shaping policy decisions to enrich student experiences in the era of AI integration.
Keywords: dept.mrk; peer-reviewed

Market Sensing Today - Prince, Melvin; Priporas, Constantinos-Vasilios (Business Expert Press, 2015)
Today's practicing marketers and scholars are confronted with a wide array of conflicting and imprecise information about best practices by which to search, gather, consolidate and interpret market information. Consequently, the need has never been greater to optimize market sensing to generate managerial actions that efficiently and effectively utilize knowledge of emerging consumer needs and competitive threats. This book addresses these urgent concerns. In essence, Market Sensing Today will cover, in ground-breaking ways, the following marketing managerial areas: * marketing opportunities associated with conventional and progressive bases of segmentation. * trends in market segment size and growth affecting long-range planning. * strategic direction for reaching future goals. * managerial understanding of assumptions competitors make about themselves. * the direction of current market strategies. * adding to the knowledge of a firm's core competencies. * how new market knowledge is best integrated into a firm's market intelligence system. * best ways to ensure the quality of information underlying decisions. * how benchmarking improves with market sensing. * best approaches for translating business issues into projects. * ways that key information may be disseminated within firms. * how proposed strategic changes are promoted by market sensing. * roles customer satisfaction insights play in policy. This book will address these key issues and more, to advance theory, research and practice based on latest developments in this vital field. It will show how to re-formulate traditional models that no longer work.
Keywords: dept.mrk; faculty_collection

Political Polarization: Challenges, Opportunities, and Hope for Consumer Welfare, Marketers, and Public Policy - Weber, T.J.; Hydock, Chris; Ding, William; Gardner, Meryl; Jacob, Pradeep; Mandel, Naomi; Sprott, David E.; Van Steenburg, Eric (Journal of Public Policy & Marketing, 2021)
Political polarization is a marked political division in the population, characterized by multiple manifestations. The authors argue that it can affect consumer psychology, which in turn influences marketers, policy makers, and consumer welfare. The present work introduces the construct of political polarization to the marketing literature and shows how it serves as a novel challenge for various marketing stakeholders. For consumers, the authors propose that political polarization increases the salience of political identities, alters inter- and intragroup dynamics, and amplifies cognitive biases. These effects negatively affect consumer welfare, including financial welfare, relationships, mental and physical health, and societal interests. For marketers, polarization introduces a challenge to both be more sociopolitically engaged while also navigating competing political interests. Polarization also creates new opportunities and challenges for segmentation, targeting, loyalty, and product offerings. For policy makers, political polarization creates policy gaps, impedes the implementation of policy, and obstructs governance. Building from these insights, the authors consider the drawbacks and overlooked benefits of political polarization, potential remedies, and directions for future research.
Keywords: dept.mrk; peer-reviewed

Threat appraisal, emotional contagion, and Fear of COVID-19: Revision of the Extended Parallel Process Model - Prince, M.; Kim, Y. (Journal of Applied Social Science, 2023)
Fear of COVID-19 has been understandably widespread, given continual exposure to dire information from pandemic media coverage and interpersonal communications. The present study addresses a limitation of the extended parallel process model in predicting fear of COVID-19 by inclusion of the concept of emotional contagion. The main gap in the literature is filled by the study’s distinctive contribution that broadens and upgrades the extended parallel process model. The model is extended by its integration with the theory of emotional processing. The study is based on a national panel of adults (N = 206). The methods include path modeling by SmartPLS. In addition, multigroup analyses examine overall model differences between gender classifications. Findings and conclusions can be used to minimize excessive fear, and at the same time to promote confidence in following official public guidance and protective regulations to cope with the pandemic. © The Author(s) 2023.
Keywords: cognitive; dept.mkt; emotional contagion; fear; motivation; peer-reviewed; threat appraisal

Today's Business Communication: A How-to Guide for the Modern Professional - Snyder, Jason L.; Forbus, Robert (2013 digital library, 2014)
This handy guide to excellent business communications is perfect for both college students and business professionals. Whether preparing for a career, launching a career, or advancing in a career, the savvy professional understands that every organization expects employees to be exceptional business communicators. Today's Business Communication: A How-to Guide for the Modern Professional leads readers through the most frequently encountered business communication situations. Two business partners who are also business school professors share their combined 30 years of marketing and communication experience with readers in this accessible, entertaining, and informative guide. The authors enhance the readers' experience through anecdotes from business professionals from different industries.
Keywords: Business communication; dept.mkt; faculty_collection

An Assessment of the Ecosystem for Social Entrepreneurism in Alabama's Black Belt - Forbus, Robert; Snyder, Jason L. (Alabama State University, Center for Leardership and Public Policy, 2012)
Keywords: Alabama; Alabama; Entrepreneurship; Ecosystem health; dept.mkt; faculty_collection

Study Abroad: A Path to Lifetime Learning - He, Xiaohong; Jackson, Anita L.; Lodha, Shyam S. (University Of Connecticut Center for International Business Education and Research, 2004)
Keywords: Foreign countries; Foreign study; American students; dept.mkt; faculty_collection

Secondary Risk in COVID-19 Vaccination Intentions: A Theoretical Contribution to the Protection Motivation Paradigm - Prince, Melvin; Kim, Young (Journal of Applied Social Science, 2023)
This study presents an original model that features the emotion of fear of COVID-19 as a direct effect on vaccination intentions. A central research question addressed in the study is what roles do the emotion of fear of contracting COVID-19 and the threat posed by uptake of the COVID-19 vaccination play in levels of vaccination intention? The study used a structural equation model (SEM) and applied the SmartPLS 3.2.6 data analysis tool for model estimation and multivariate analysis variables. A key finding is that vaccination resistance is strongest when fear of COVID-19 is lower, and vaccination threat higher. Vaccination threat appraisal and vaccination intention were found to have a negative relationship. Response costs at higher levels lessen motivation for COVID-19 vaccination. Research implications include research-based targeting of differing segments by their primary fear, either fear of COVID-19 or of the preventative vaccine.
Keywords: dept.mkt; peer-reviewed

Ethical marketing AI? A structured literature review of the ethical challenges posed by artificial intelligence in the domains of marketing and consumer behavior - Su, Y.; Wang, E.; Berthon, P. (Proceedings of the Annual Hawaii International Conference on System Sciences, 2023)
With the increasing use of AI in marketing, ethical repercussions are beginning to emerge. From privacy issues, through discrimination of marginalized groups, to emergent systemic social distortions, AI is changing the marketing ethical landscape. In this paper we conduct a structured literature review of the emerging ethical issues posed by AI in the domains of marketing and consumer behavior. We identify three clusters of ethical issues (algorithm, society and existential) and map these to the marketing domains of systems, brands, and consumers. We conclude that the field of ethical marketing AI is still very much in its infancy, but such is the rate of development ethical marketing AI is likely to become an important field for academics and practitioners alike. © 2023 IEEE Computer Society. All rights reserved.
Keywords: AI; Consumer Behavior; Ethics; Marketing; dept.mkt

Does polarizing personality matter in influencer marketing? Evidence from Instagram - Koorank Beheshti, Mohammadali; Gopinath, Mahesh; Ashouri, Sama; Zal, Saeed (Journal of Business Research, 2023)
Social media platforms have become more polarizing with the emergence of polarizing influencers. This research investigates how polarizing influencers can improve the effectiveness of brand-posts with the help of three experiments and field-data from Instagram. The results of the first experiment suggest that the polarizing nature of the communication source triggers defensive motivated reasoning among fans, even when the message being communicated is non-polarizing. This, in turn, has downstream consequences on post engagement and purchase intention. Analysis of 779 brandposts of Instagram influencers suggests that the polarization effect on post engagement is stronger for mega (vs. macro) influencers. By exploring the role of motivated reasoning, this research expands our understanding of the factors that drive consumers to engage with brand content on social media. The findings suggest that marketers can take advantage of the existing polarization among online users regarding polarizing influencers to enhance the effectiveness of their brand communication.
Keywords: Defensive motivated reasoning; Group polarization; Influencer marketing; Source characteristics; dept.mkt; peer-reviewed

Co-branding partners: What do they see in each other? - Prince, M.; Davies, M. (Business Horizons, 2002)
The decision about whether to co-brand is based on two conditions: the opportunities for creating a competitive advantage, and the operational benefits that will result. When these conditions are favorable, a firm must pick the right co-branding partner, using such criteria as (a) compatibility between brands, (b) market volatility, (c) investment requirements and arrangements, and (d) the prospective partner's commitment to the agreement. The firm and its chosen partner then enter the phase of courtship and potential conflict, which involves planning, negotiation, and conflict avoidance and management. Finally, they must create an exit strategy, in case the co-branding arrangement fails to live up to its promise.
Keywords: dept.mkt; peer-reviewed

Diamond geezers - Prince, M. (Business Strategy Review, 2005)
Keywords: dept.mkt

Switching costs: A key to understanding and managing business consulting relationship longevity - Prince, M.; Everett, R.F. (Adv. Bus. Mark. Purch., 2012)
In consultant-client relationships, relationship longevity can create significant cost advantages and operational efficiencies for both client and consultant. At the same time, each party may also be motivated to look for new perspectives and opportunities by switching to new relationships. However, the benefits of replacing one consulting relationship with another are mitigated by switching costs: the costs associated with the act of changing the relationship itself. This chapter explores the concept of switching costs by examining various types of costs, the ways these costs have been conceptualized in the literature, and how these costs may impact the nature and continuity of consultant-client relationships. The chapter will end with a series of hypotheses and suggestions for a research agenda to further develop our understanding of this important phenomenon. Copyright © 2012 by Emerald Group Publishing Limited.
Keywords: dept.mkt

How shopping satisfaction contributes to internationaltourism satisfaction and tourism expenditures by gender: Analysis of U.S. tourists in South Korea - Middaugh, J.; Kwak, L.E.; Meng, F. (International Journal of Business Research, 2013)
The purpose of the study was to examine how international tourists' shopping satisfaction related to their overall satisfaction as tourists and the tourists' expenditure differences by gender. A survey was conducted among U.S. citizens of who were traveling to South Korea (n = 422). The survey took place at transport hubs of the major international airports and seaports in South Korea prior to tourists' departure. The findings of this research concluded that tourist shopping satisfaction was significantly correlated with overall tourist satisfaction. In addition, different shopping patterns were reported among men and women tourists. The results of this study confirm that a positive retail shopping experience is an important aspect of overall international tourism.
Keywords: Gender; Shopping satisfaction; United States tourists; dept.mkt; peer-reviewed

Metaphor elicitation: A new way to assess organizational culture - Prince, M.; Forr, J. (Psychologist-Manager Journal, 2021)
The purpose of this paper is to advance breakthrough research that further extends, as well as enrichens, our understanding of organizations. This is a companion article to “CEO Archetype Identity Drives Organization Culture” previously published in this journal. Archetypes are merely a special case of metaphors. In this paper, we generalize the concept of leadership archetypes to organization metaphors, adding original dimensions to existing concepts and theories of organizational diagnosis. Thus, the present research brings a new enlightening perspective to this field. Data from the past organization studies featured in this article involve the Zaltman Metaphorical Elicitation Technique (ZMET) embedded in qualitative in-depth personal interviews. These studies explore the impact of management styles on organization structure and functions. In each study metaphors were elicited from leaders and followers, and generated insights and action-oriented strategies to meet organizational challenges © 2021. American Psychological Association
Keywords: dept.mkt; peer-reviewed

A longitudinal reliability study of a consumer disidentification model - Prince, M.; Kwak, L. (Journal of Empirical Generalisations in Marketing Science, 2022)
Josiassen (2011) in a single cross-sectional survey investigated causal relations between consumer disidentification and domestic product judgments. The primary purpose of this replication paper is to evaluate the reliabilities of construct levels, as well as the significance, direction and magnitude of causal effects advanced in the original published structural model. The study measures relations between consumer disidentification (CDI) and domestic product judgments of American products over an extended 16 months period among second generation immigrants. In the present research the original CDI model fit was found to be longitudinally consistent and stable. Serendipitously, findings of the present study disclosed that over time baseline levels of consumer disidentification vary and actually declined significantly. Additionally, the negative effect of consumer disidentification on American product judgments significantly weakened over the course of the study. As an additional test of consumer predisposition reliability over time, the model in this study incorporated consumer xenocentrism (XEN) as a second predictor variable of domestic product judgments. Findings of this analysis were consistent with those found for CDI. These new phenomena have important theoretical and managerial implications. © 2022, University of South Australia. All rights reserved.
Keywords: dept.mkt; peer-reviewed; ⛔ No DOI found

Leading Edge Marketing Research: 21st-Century Tools and Practices - Kaden, Robert J.; Linda, Gerald; Prince, Melvin (SAGE Publications, 2012)
This book explores new and leading edge marketing research approaches as successfully practiced by visionaries of academia and the research industry. Ideal as either a supplementary text for students or as a guidebook for practitioners, this book showcases the excitement of a field where discoveries abound and researchers are valued for solving weighty problems and minimizing risks. The authors offer rich new tools to measure and analyze consumer attitudes, combined with existing databases, online bulletin boards, social media, neuroscience, radio frequency identification (RFID) tags, behavioral economics, and more. The reader will profit from the numerous contemporary case studies that demonstrate the key role of marketing research in corporate decision-making.
Keywords: Business & Economics / Marketing / Research; Marketing research; dept.mkt; faculty_collection

Consumer Cosmopolitanism in the Age of Globalization - Prince, Melvin (Consumer behavior collection, 2012)
Cosmopolitans are individuals with a distinctive kind of extended national and international orientation, a global vision, and sense of belonging to the world. These people are sophisticated and importantly engaged in the cultures outside of local geographical boundaries. But what do we know about them as consumers—their origins, values, media usage, and buyer behavior? This unique book details much about this group, and fills a knowledge gap that has long been overlooked largely because other related marketing areas have overshadowed and overlooked the notion of cosmopolitan consumers. Until this book, in fact, there has been no single authoritative source that directly and comprehensively covers the field of consumer cosmopolitanism. This book also includes original essays by an all-star cast of contributors, giving you an introduction to a powerful new approach to marketing, eclectically packed with novel ideas and insights that noticeably advance the marketing field and bring it more fully into the age of globalization.
Keywords: Business & Economics / Consumer Behavior; Consumer behavior; dept.mkt; faculty_collection

Continuties in Market Sensing - Prince, Melvin; Priporas, Constantinos-Vasilios (Market Sensing Today, 2015)
The concept and framework of market sensing was introduced by George Day more than 20 years ago into the strategic marketing literature and especially the philosophy of the market-driven organization. Market sensing can be considered an expression of a company's capabilities to scan the external environment. It does this by using real time data and intelligence to understand business or uncertain changes, to meet the current and future needs of the market, increase customer value, and outperform competitors. Market sensing enables managers to resist complacency, as well as to exploit opportunities and to design appropriate competitive strategies in order to remain successful in today's uncertain, rapidly changing, and hypercompetitive market. The present volume, Market Sensing Today, is essential reading in the marketing discipline, given the rapidly escalating innovative developments in market sensing techniques. This book of essays by acknowledged experts in the field fills an important knowledge gap and provides a realistic basis for strategy. It is replete with real-life examples of market sensing that illustrate actionable ideas for immediate impact that will improve organizational learning and accelerate growth. This book of contemporary tested and comprehensive concepts and methods grounded in diverse and rich experience is intended to stimulate creativity and insightful approaches for educators offering courses in strategy as well as for practitioners involved in crucial strategic decision making.
Keywords: Business & Economics / Marketing / General; Marketing research; dept.mkt; faculty_collection

Industry Applications of Market Sensing Foreword to the Special Issue of Journal of Marketing and Management - Prince, Melvin; Priporas, Constantinos-Vasilios (Journal of Marketing and Management, 2014)
Keywords: Business And Economics--Management; Business And Economics--Marketing And Purchasing; Competition; Competitive advantage; Consumers; Knowledge management; Marketing; Product development; Product lines; Research; SWOT analysis; dept.mkt; ⛔ No DOI found

The effect of mindfulness on service encounter quality - Wang, Emma Junhong; Berthon, Pierre R.; Bechwati, Nada Nasr (Journal of Services Marketing, 2020)
Purpose This paper aims to explore the effect of employees’ state mindfulness, a short period of mindful presence, on the quality of the service they provide in a service encounter. Design/methodology/approach Three studies are conducted. A pilot study explores the relationship between state mindfulness and service encounter quality. Experiment 1 examines whether a 15-min mindfulness exercise results in an increase in service employees’ state mindfulness. Experiment 2 tests whether induced state mindfulness produces higher service quality and whether a reminding technique can prolong state mindfulness between service encounters. Findings The results demonstrate the following. First, that more mindful employees provide better service quality. Second, that a short, easily implemented, mindfulness exercise can reliably increase employees’ state mindfulness. Third, induced mindfulness has an impact on subsequent service quality in terms of reliability, assurance, empathy and responsiveness. These effects persist regardless of the service encounter structure (high vs low structure) or the degree of emotional labor involved (high vs low emotionally charged). Finally, the reminding technique developed as part of this research suggests that state mindfulness can be maintained between service encounters. Research limitations/implications As simulated (programmed) customers are used, independent evaluators to assess service quality are used. Service providers in this study are college students; future field studies should consider a wider range of service providers. The research focuses on state mindfulness; exploration of trait mindfulness offers future research opportunities. Originality/value To the best of the authors’ knowledge, this research is the first to empirically examine the link between mindfulness and service quality. It shows that mindfulness can be induced, and through a reminding technique be maintained, and improve service quality across service interactions. This is a powerful finding for marketing managers, for it offers a new method to enhance service provision. Moreover, this research implies that the increase in service quality is likely to be accompanied by reduced job burnout: a double win for employees, employers and customers.
Keywords: Emotional labor; Induced state mindfulness; Mindfulness; Service encounter quality; Service encounter structure; dept.mkt; peer-reviewed

Exploring the optimized social advertising strategy that can generate consumer engagement with green messages on social media - Kyu Kim, Young; Yim, Mark Yi-Cheon; Kim, Eunjin; Reeves, William (Journal of Research in Interactive Marketing, 2020)
Purpose: Given that many consumers are skeptical about environmentally based advertising campaigns, the purpose of this study is to propose an optimized message strategy to facilitate consumer engagement with green messages in social media contexts. Design/methodology/approach: Four empirical studies are conducted using self-report questionnaires to test proposed hypotheses with a focus on the interplay between claim specificity and benefit appeals in green advertising on social media. Findings: The current study examines the interaction effects of claim specificity and benefit appeals on consumer engagement in social media. Specifically, the results reveal that when the message claim is abstract, using other-benefit appeals produces more positive consumer engagement than using self-benefit appeals. Moreover, the results illustrate that self-enhancement motivates consumers to engage with green product advertising messages when the advertising appeal is abstract and the advertising message is associated with benefits for others. Finally, it is found that consumers’ self-construal level moderates the interaction effect of claim specificity and benefit appeals type on consumer engagement on social media. Practical implications: This paper has practical implications to both social media managers and advertisers in the green product industry: a match with advertising claim specificity and construal level (i.e. social distance: self-benefit vs other-benefit) should be ensured to increase consumer engagement on social media. In addition, self-enhancement and self-construal should be considered for a better message strategy in social media contexts. Originality/value: The findings make important contributions to the literature in that we extend the applications of construal level theory to social media contexts as a valid theoretical tool to identify optimized green message strategies. As such, it provides future researchers and practitioners in the domain of green campaigns with useful guidelines to boost more consumption of green products. © 2020, Emerald Publishing Limited.
Keywords: Online consumer behavior; Social media advertising; dept.mkt; peer-reviewed

Impact of risk aversion, reactance proneness and risk appraisal on travel destination risk perception: - Prince, Melvin; Kim, Young Kyu (Journal of Vacation Marketing, 2021)
The aim of the study is to investigate the motivational effects of tourist traits and risk appraisal on tourist destination risk perception. Risk appraisal involves subjective estimates of vulnerability to a threat and the threat’s consequential severity. Fear levels influence both of these elements of risk appraisal. Individual differences in reactance proneness and risk aversion are introduced into the study model to more fully account for differences in travel destination risk perceptions. The study design involves US adults, who have used their passports for international travel in the past 5 years. Travel risk assessments were studied for four destination sites: London, Tokyo, Kuala Lumpur and Istanbul. A general structural model is developed to test hypotheses about antecedents and consequents of risk appraisal and destination risk perception. © The Author(s) 2021.
Keywords: dept.mkt; peer-reviewed

Cultural adaptation and consumer disidentification in the us - Prince, M.; Kwak, L (Journal of Empirical Generalisations in Marketing Science, 2020)
Alexander Josiassen (2011) initiated research on the consumer disidentification (CDI). More specifically, in his investigation of 2nd generation Turks in the Netherlands, he introduced the concept of acculturation as an antecedent to consumer disidentification among this ethnic group. Josiassen's study showed that acculturation negatively affects CDI. The present replication research among American 2nd generation US immigrants confirmed Josiassen’s findings with respect to CDI. It also confirmed his findings that acculturation positively affects consumer ethnocentrism (CET). In elaborating his model, the US study found that (a) national disidentification (NDI) is inversely predictive of acculturation, and (b) acculturation is negatively predictive of consumer xenocentrism (XEN). Replication of the Netherland CDI model in the U.S. results in an acceptable measurement fit and structural fit. © 2020, University of South Australia. All rights reserved.
Keywords: Consumer disidentification; Cross-cultural; Ethnocentrism; National disidentification; Xenocentrism; dept.mkt; peer-reviewed; ⛔ No DOI found

Consumer responses toward symmetric versus asymmetric facial expression emojis - Hewage, G.S. Urumutta; Liu, Yue; Wang, Ze; Mao, Huifang (Marketing Letters, 2021)
Facial expression emojis are commonly used in digital communications and marketing campaigns. However, it is less known how the design of emojis may affect consumer responses. To address this gap, this research examines the impact of emojis’ facial asymmetry levels on consumer judgments. Findings across four studies demonstrate that compared with their symmetric counterparts, asymmetric facial expression emojis are more likely to receive favorable consumer evaluations. This effect is driven by perceptions of human expression resemblance and emotional expression strength and tends to be more prominent among consumers with a higher level of emotional sensitivity. Moreover, marketing messages including an asymmetric (vs. a symmetric) emoji are more likely to generate positive consumer responses.
Keywords: dept.mkt; peer-reviewed

Marketing mix standardization: a cross cultural study of four countries - Kustin, Richard Alan (International Business Review, 2004)
The study researched the possibility of standardizing the marketing mix by investigating the cross-cultural responses from the United States, Brazil, France and India. The study tested the premise of standardization by determining if respondents perceived specific attributes of a common non-durable consumer product the same or differently. The results indicate the opportunity for dynamic marketing standardization remains limited but applicable within specific cultural country markets. Several attribute perceptions between US and foreign respondents are found to be more similar than dissimilar suggesting advantages may exist for a limited implementation of marketing mix standardization as part of a global marketing strategy. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Consumer product; Cross-culture; Globalization; Hofstede; International marketing; Marketing mix; Standardization; dept.mkt

The animal within - Prince, Melvin; Davies, Mark (Business Strategy Review, 2004)
Keywords: dept.mkt

Consumer Income and Beliefs Affecting Happiness - Prince, Mel; Manolis, Chris (Advances in Quality-of-Life Theory and Research, 2003)
Recent syntheses of empirical studies have clearly demonstrated a consistently positive relationship between income and happiness. Research is needed to reduce uncertainty and disentangle such relationships, which have been found to be quite modest, but significant in the aggregate. The present study contributes to this end, in that it investigates the moderating effect of income on the relationship between beliefs that serve as internal buffers and happiness. We go beyond simple associations of income and happiness to examine relationships between income and self-esteem and between income and optimism. Finally, causal modeling is employed to demonstrate that, under varying income levels, these beliefs affect happiness by the same process — with distinct yet predictable outcomes.
Keywords: beliefs; causal model; dept.mkt; happiness; income; money

A model of job performance, job satisfaction, and life satisfaction among sales and sales support employees at a pharmaceutical company - Prince, Melvin; Engle, Robert L; Laird, Kenneth R (Journal of Pharmaceutical Marketing & Management, 2003)
This study investigates the influence of role conflict, role ambiguity, and role strain on job performance, job satisfaction, and life satisfaction among field sales and company sales support employees in a single pharmaceutical company. Because this study is based on data from a single company, these results may not necessarily be generalized to all companies in the industry. In the present research, a path model of the process reveals important variations in response to role conflict, role ambiguity, and role strain between the two classes of employees. For both classes, the influence of decreased role ambiguity is generally positive for measured outcomes. However, reductions in role conflict, while lessening role strain, are likely to result in lower job performance for field sales employees. Decreases in role strain, while improving life satisfaction, may lead to lower job satisfaction for sales support employees. © 2003, Informa UK Ltd All rights reserved: reproduction in whole or part not permitted. All rights reserved.
Keywords: Job performance; dept.mkt; job satisfaction; life satisfaction; pharmaceutical sales; role strain

Factors affecting encoding, retrieval, and alignment of sensory attributes in a Memory‐Based brand choice task - Shapiro, Stewart; Spence, Mark T. (Journal of Consumer Research, 2002)
Sensory attributes, such as sound quality ascertained by listening to a stereo, are often ambiguous and therefore difficult to encode and retrieve. Despite this, consumers often place more weight on these attributes compared to verbally described market information when making brand choice decisions. Results from two studies demonstrate that providing criteria to evaluate the sound quality of competing brands of stereos facilitates the encoding, retrieval, and alignment of the sensory attribute in a brand choice task. Study 1 shows that without criteria to evaluate sound quality during trial, memory for this attribute is poor. Further, perceptions of sound quality assimilate to conflicting market information, which adversely affects decision performance. The reverse is true when evaluative criteria and a scheme to rate the criteria are provided: memory for sound quality improves, perceptions of sound quality contrast with conflicting market information, more weight is placed on sound quality when decision making, and better choices are made. Study 2 shows that providing evaluative criteria during product trial enhances performance through improvement in the encoding process.
Keywords: dept.mkt; peer-reviewed

Moderator teams: an extension to focus group methodology - Prince, Mel; Davies, Mark (Qualitative Market Research: An International Journal, 2001)
Traditional focus group methodology involves an individual trained moderator who manages the whole process from writing the focus group guide that directs the topics pursued, the interaction with participants, to interpretation, reporting and client feedback. Since their training, personality and orientation can vary differentially, this may lead to moderator bias. Proposes a new method that involves a series of complementary moderators that target specific areas of the guide that allows them to specialise in their particular experiences and orientations. These moderators are used sequentially on the same groups that offer the potential to avoid many of the problems associated with single-moderator discussion groups. Moreover, the chance to moderate the moderator keeps a check on how the sessions of each focus group develops, building in feedback between moderators, and reduces the prospects of misinterpretation and side-tracking by a single moderator. © 2001, MCB UP Limited
Keywords: Equal value; Focus groups; Management; dept.mkt

The entry of international CPA firms into emerging markets: motivational factors and growth strategies - Kirsch, Robert J; Laird, Kenneth R; Evans, Thomas G (The International Journal of Accounting, 2000)
This article examines the entry of professional service firms, specifically the Big Six international accounting firms, into emerging foreign markets and explores how they develop and expand their business once established in those markets. The study is based on survey data (supplied by the Big Six) regarding their penetration of the People's Republic of China, the Commonwealth of Independent States, and Central Europe. A conceptual model is employed to illustrate the interrelationship between a firm's specific characteristics, the foreign environment, and foreign subsidiary intrafirm structure. Growth potential, client needs, favorable political/legal climate, and cultural considerations emerged as important factors in determining market entry and growth strategies for professional services firms. The research findings broaden our understanding of factors that influence professional services firms' development of pricing and marketing mix strategies. While all firms surveyed offered a full range of services, their marketing mix strategy differed from domestic approaches because of various local constraints on pricing and promotion. Copyright © 2000 University of Illinois.
Keywords: Commonwealth of independent States; Eastern European and Baltic States; International market entry and expansion; International marketing of accounting services; Marketing mix strategies of professional services firms; People's Republic of China; dept.acc; dept.mkt

A marketing resource-based model of international market entry and expansion for professional services firms - Laird, Kenneth R; Kirsch, Robert J; Evans, Thomas G (Services Marketing Quarterly, 2003)
This paper examines the entry of the Big Six international accounting firms, into emerging foreign markets and explores marketing resource considerations once established in those markets. The study is based on survey data (supplied by the Big Six) regarding their penetration of the People's Republic of China, the Commonwealth of Independent States, and Central Europe. The paper presents a marketing resource-based model based upon relevant research. The model focuses on firm specific resource capabilities interacting with the foreign business environment and the foreign intrafirm structure as a determinant of foreign market entry choice and eventual market expansion. The research findings broaden our understanding of factors that influence professional services firms' development of marketing resource strategies when expanding globally. While all firms surveyed offered a full range of services, their marketing resource strategy differed from domestic approaches because of various local constraints on marketing mix elements. © 2003 Taylor & Francis Group, LLC.
Keywords: Commonwealth of Independent States; Eastern European and Baltic states; International market entry and expansion; International marketing of accounting services; Marketing mix strategies of professional services firms; People's Republic of China; dept.acc; dept.mkt

A latent class analysis of brand prestige - Prince, Melvin; Davies, Mark (Model Assisted Statistics and Applications, 2009)
Core constructs are necessary as a basis for scale development in brand prestige research. This study examines the theoretical rationale for two such concepts - brand excellence and status conferral - and uses latent class scaling in an empirical test as to whether they are both important independent dimensions of prestige brands. Based on the analysis, these concepts are shown to be consistently present for two brands in two diverse product categories. The research calls into question earlier work on the measurement of brand prestige that was premised on a one-dimensional concept of prestige. Further studies are needed to explore the dimensionality and substantive structure of the brand prestige concept, to confirm or disconfirm findings from this research. © 2009 IOS Press. All rights reserved.
Keywords: Brand excellence; Latent class scaling; Prestige brand; Status conferral; dept.mkt

Qualitative analysis and the construction of causal models - Prince, Melvin; Manolis, Chris; Tratner, Susan (Qualitative Market Research: An International Journal, 2009)
Purpose: The purpose of this paper is to provide a methodology by which qualitative analyses serve as rich source materials for discovery of theoretically cogent interrelations between latent variables. Design/methodology/approach: In an illustrative case, qualitative data are collected from US franchisee managers from a single branded franchise of automotive repair outlets. Qualitative analysis of franchisee experiences and attitudes is critical for construction of a causal model used to predict conflict intensity between franchisee managers and franchisors. Findings: The model is based on franchisees' normative expectations for resource allocation within the franchise; and their perceptions of franchisor normative violations, which are determinative of grievances, distrust, and hostility. This theoretical orientation serves to generate a system of interrelated empirically testable propositions. Research limitations/implications: In principle, the primary limitation of using qualitative analysis for the construction of causal models is the fruitfulness of the theoretical orientation shared by the qualitative analyst and the causal modeler. Practical implications: The methodological approach advanced in this paper advances qualitative research and causal modeling beyond the individual contributions. Qualitative analysis infuses variables and process imagery into causal modeling. In turn, causal modeling elaborates the qualitative analysis and makes explicit logical connections between variables. Originality/value: This paper advances a methodology by which qualitative analysis and causal model construction may be usefully integrated. Theory-based qualitative analysis may be formalized to map latent concepts and their interrelations. Further, operational measures of these concepts may be adduced from the analysis of textual data. © Emerald Group Publishing Limited.
Keywords: Modelling; Qualitative methods; dept.mkt

A study of hofstede's culture value survey in a post-soviet country - Kustin, Richard Alan (Journal of Transnational Management, 2006)
This research examines the four culture dimensions developed by Hofstede's 1980 and 1983 studies exploring the potential of management-employee conflict. In the present study, employee responses to Hofstede's national culture survey were performed in Belarus, formerly of the Soviet Union, in order to establish a culture score for each of Hofstede's four culture dimensions in a centrally planned economy. The results of the research run counter to some of the stereotypic cultural characteristic expectations, and support others of the cultural values attributable to the Republic of Belarus, an autocratic political and economic state in Eastern Europe. Copyright © by The Haworth Press, Inc. All rights reserved.
Keywords: Belarus; Cross culture; Cultural survey; Culture dimensions; Eastern Europe; Eurasia; Europe; Hofstede; International management; culture; dept.mkt; geographical research; survey

Genetically modified crops’ environmental impact and trust in eco-labels - Kwak, Lynn E.; Yoon, Sang Won; Kim, Younjun (Australasian Marketing Journal, 2020)
The U.S. Department of Agriculture expects companies to disclose genetically modified (GM) ingredients in foods and beverages by January 2022. While food companies fear that the stigma of GM labels could cause GM food sales to decline, eco-labeling could lessen the impact of GM-labeling. The results of the present research indicate that neither the eco-labeling alone nor the eco-labeling accompanied by information about the environmental benefits of GM crops influence consumers’ willingness to buy. Based on the mediation analysis, however, trust of eco-labels mediates the relationship between GM foods’ environmental friendliness information and consumers’ willingness to buy eco-labeled GM food. The theoretical and practical implications of the findings are discussed. © 2020
Keywords: Eco-labeling; Genetically modified (GM) foods; Trust; Willingness to buy; dept.eco; dept.mkt; peer-reviewed

Domestic Product Involvement and Consumer Willingness to Buy Domestic Products: Empirical Testing of a Cognitive Consistency Theory Framework - Prince, Melvin (Journal of International Consumer Marketing, 2020)
This study investigates biases affecting domestic products willingness to buy (WTB). An interdisciplinary perspective uses the cognitive consistency theory as the framework for the development of a new model. The model includes domestic product involvement (DPI). The impact on WTB is predicted by consumer ethnocentrism, and product judgment, driven by DPI are tested with survey data from an adult sample of 255 UK consumers. The study concludes with observations about the value of research findings for marketing practice. © 2020 Taylor & Francis Group, LLC.
Keywords: Cognitive consistency theory; consumer ethnocentrism; dept.mkt; domestic product involvement; peer-reviewed; product judgment; willingness to buy

Does the Netherlands-based consumer disidentification model work in the US? - Prince, Melvin; Kwak, Lynn (EMPGENS | Journal of Empirical Generalisations in Marketing Science, 2020)
Alexander Josiassen (2011) initiated research on the consumer disidentification (CDI) concept and its impact on product purchase behavior. In his investigation, a predictive model that included CDI as an exogeneous factor in domestic product preference was tested on adult second-generation immigrants who were born in, and lived in, the Netherlands. The model also incorporated consumer ethnocentrism (CET) as a second predictor variable. Josiassen's study showed that CDI negatively affected the purchase of products made domestically or by domestic firms. Conversely, CET was found to have a positive effect on the purchase of these products. Furthermore, relationships of CDI and CET to purchase intentions were independent of each other. In the Netherlands model, both variables were hypothesized to explain domestic product preference directly and indirectly through domestic product judgment. This paper replicates and assesses the generalizability of the CDI construct and model. Replication of the Netherland CDI model in the U.S. results in an acceptable measurement fit, but a slightly below acceptable structural fit. © 2020, University of South Australia. All rights reserved.
Keywords: Consumer disidentification; Cross-cultural; Domestic product preference; Ethnocentrism; Second-generation immigrants; dept.mkt; peer-reviewed; ⛔ No DOI found

The psychology of consumer ethnocentrism and cosmopolitanism: a five-country study of values, moral foundations, gender identities and consumer orientations - Prince, Melvin; Yaprak, Attila; Cleveland, Mark; Davies, Mark A. P.; Josiassen, Alexander; Nechtelberger, Andrea; Nechtelberger, Martin; Palihawadana, Dayananda; Renner, Walter; Supekova, Sona Chovanova; Von Wallpach, Sylvia (International Marketing Review, 2020)
Purpose: The purpose of this paper is to examine the extent to which personal values, moral foundations and gender-role identities affect, in sequence, consumers' constructions of their ethnocentric and cosmopolitan orientations. Achieving a better understanding of the psychological makeup of consumer ethnocentrism and cosmopolitanism should help managers better design international market segmentation and brand positioning strategies. Design/methodology/approach: The study's conceptual framework is anchored in attitude and values theories, and focuses on the social categorizations that consumers make and how these contribute to the formation of their ethnocentric and cosmopolitan orientations. Drawing data from consumers living in five European countries, we test our theoretical conjectures through structural equation modeling approaches, including multigroup analysis at the country level, as well as the identification and scrutiny of potential pan-European consumer segments. Findings: Findings show that personal values, moral foundations and gender-role identities do exert direct and indirect (partially mediated) effects on the formation of consumers' ethnocentric and cosmopolitan orientations. These provide numerous insights for managers in terms of how they can segment domestic and international markets, as well as how to position products and communicate brand strategies. Research limitations/implications: The study focused on consumers' personal and role identities and offers implications based on data gathered from a sample of five European countries. Future work should broaden this perspective by including other identity facets, such as religious and ethnic identities, as well as product-category and brand-specific outcomes, in order to help develop a more comprehensive picture of the psychology underpinning consumers' identity-related orientations, and their effects on consumer behavior. Future research should also study these issues in a broader geographical context, by including national markets that have culturally diverse populations as well as places with dissimilar cultural and economic profiles. Originality/value: The study shows that individuals' personal values, moral foundations and gender roles have a strong effect on the formation of consumer ethnocentrism and consumer cosmopolitanism orientations. Consideration of how these antecedent constructs operate in concert to shape consumers' in- versus out-group orientations has been overlooked in the international marketing literature. Beyond the ramifications for theory, the study offers numerous substantive managerial implications in terms of how consumers are likely to respond to local and global/foreign products/brands based on these orientations. © 2020, Emerald Publishing Limited.
Keywords: Consumer cosmopolitanism; Consumer ethnocentrism; Gender role identity; International market segmentation; Moral foundations; Values; dept.mkt; peer-reviewed

How to easily facilitate consumers’ mental simulation through advertising: the effectiveness of self-referencing image dynamics on purchase intention - Yim, Mark Yi-Cheon; Kim, Young K.; Lee, JeongGyu (International Journal of Advertising, 2020)
Keywords: dept.mkt; peer-reviewed

Dependence and interdependence in marketing relationships: meta-analytic insights - Scheer, Lisa K.; Miao, C. Fred; Palmatier, Robert W. (Journal of the Academy of Marketing Science, 2015)
The authors conduct a meta-analysis to examine dependence and interdependence in marketing relationships. Analyses reveal that dependence affects performance primarily through relationship quality and cooperation, while interdependence has substantial direct effects as well as effects mediated through relationship-specific investments and cooperation. Regarding relationship context, effects of dependence are stronger in channel relationships than end-user relationships and for services than goods; interdependence does not display the same pattern. Regarding methodological context, dependence measures that emphasize relationship value versus switching costs have different moderating effects; greater general dependence content is associated with weaker effect sizes for dependence but conversely greater effect sizes for interdependence. These results suggest that new insights can be gained by distinguishing relationship value and switching cost components of dependence and by investigating the possibility that the conceptual domain of interdependence differs from that of dependence. Future research that strives for greater precision in the measurement of dependence and interdependence constructs and that simultaneously examines dependence and interdependence is recommended.
Keywords: Channels; Dependence; Interdependence; Measurement; Meta-analysis; Relationship value dependence; Relationships; Switching cost dependence; dept.mkt

Here, There and Everywhere: The Polycentric Consumer - Cleveland, Mark; Prince, Melvin (Springer International Publishing, 2016)
Identity is recognized as a powerful antecedent of behavior. Social identity denotes the incorporation of culture into a person’s self-concept. A strong correspondence exists between identity with a given social unit and commitment to group values/norms, and thus, how much influence the social unit exerts on the person’s attitudes and behaviors. As a psychological construct, social identity research requires probing how individuals subjectively interpret their own affiliation with one or several collectivities. Cultures are increasingly emancipated from geography in the global era. Because contemporary consumers are continuously exposed to a variety of cultural influences, they may develop polycentric identities. As companies and markets integrate, a key international market segmentation topic relates to consumers’ mindsets about home and extraneous countries/cultures, and subsequently, the products connected with these entities. To date, no research has simultaneously examined the interrelationships of consumer ethnocentrism (bias towards products from one’s national culture), consumer xenocentrism (i.e., preference or orientation towards products from a culture other than one’s own), and cosmopolitanism (i.e., a yearning for and adeptness at mastering cultural diversity) in a single study. Employing an online survey, and drawing from a representative sample (n = 269) of American consumers drawn from all 50 states (plus D.C.), this research also examines the correspondence of these identity-relevant constructs within a nomological net of pertinent concepts (all of which are established in the marketing literature): materialism, consciousness-of-kind, external orientation (cultural open-mindedness and consumption of foreign media), global consumption orientation, and natural environment concern. The survey contained a total of 60 scales corresponding to the 8 constructs, along with a series of key demographic measures. Exploratory and confirmatory factor analyses were applied to the construct measures. Various analytical techniques were employed (tests for convergent/discriminant validity, bivariate correlations, t-tests, MANOVA, two-step clustering, as well as path analyses using structural equation modelling) to test the 19 proposed theoretical hypotheses. Most hypotheses were supported, in terms of statistical significance and magnitude, as well as directional valence. Associative network memory theory and signaling theory implicate how consumers decide from a constellation of local, foreign, and global product options. Upon activation of a brand node by way of retrieval cues (product categories, brand names, and so forth), linkages such product attributes and semantic associations (e.g., ingroups/outgroups and corresponding levels of felt identification) become salient. Firms can manipulate signals, including associations towards or away from countries/cultures, to position products and persuade consumers. Vertical segmentation, the conventional approach to adapting marketing strategies, entails developing marketing mixes for each country, from the near limitless combination of demographic, economic and psychographic variables. Due to the globalization of media and the widespread movement of products and peoples across borders a growing number of researchers instead advocate horizontal segmentation, whereby similar groups of consumers are targeted with an essentially uniform marketing strategy, irrespective of where they might live. Individuals’ inward and outward dispositions—towards their own and different countries, cultures, and products—are sound candidate constructs for designing horizontal strategies.
Keywords: Consumer Ethnocentrism; External Orientation; Foreign Medium; Semantic Association; Social Unit; dept.mkt

Here, there and everywhere: a study of consumer centrism - Prince, Melvin; Davies, Mark; Cleveland, Mark; Palihawadana, Dayananda (International Marketing Review, 2016)
Purpose - A first objective is to add insight into how constructs of ethnocentrism, xenocentrism and cosmopolitanism relate to each other. Knowledge of how these constructs overlap or work together in affecting consumer preferences will offer global marketers insights for designing appropriate marketing strategies. The second objective is to extend this knowledge by examining the correspondence of these three constructs to a nomological network of dispositional concepts pertinent for product positioning and market segmentation. The third objective is to empirically examine the extent to which the measures, construct structure and associative relationships are robust in different national research settings. The paper aims to discuss these issues. Design/methodology/approach - Surveying British and American consumers, this study examines and analyzes the correspondence of these identity-relevant constructs within a nomological net of pertinent concepts: consciousness-of-kind, global consumption orientation, materialism and natural environment concern. Findings - The hypothesized negative links between CET-XEN and CET-COS, and the predicted positive connection between XEN-COS were all confirmed on the latent factor results for the combined data set. The negative correlation between CET-XEN was of a considerably lower magnitude than that for CET-COS. Originality/value - To date, no research has used an identity theory framework and simultaneously examined in a cross-cultural context the interrelationships of consumer ethnocentrism consumer xenocentrism and cosmopolitanism - and their differentiating linkages to a multiplicity of consumer dispositions.
Keywords: Cross-cultural studies; Ethnocentrism; Global marketing; Green issues; Market segmentation; Marketing; dept.mkt; peer-reviewed

An integrative framework of buyer-supplier negative relationship quality and dysfunctional interfirm conflict - Prince, Melvin; Palihawadana, Dayananda; Davies, Mark A. P.; Winsor, Robert D. (Journal of Business-to-business Marketing, 2016)
Purpose: Problems of relationship quality and interfirm conflict in business-to-business settings are serious concerns that need to be addressed. Thus, the authors have engaged in an extensive review to promote an understanding of these complex issues. This article develops an integrated framework for analyzing wide-ranging relations between individual representatives and patterns of interfirm incompatibility for managerial control.Methodology/approach: The review involves numerous sources that include articles and monographs. A theoretical framework is constructed to integrate fragmented empirical data. In particular, social identity and commitment-trust theories are mobilized for this framework.Findings: The review of studies has a substantial consistency with the theoretical framework. The article outlines a causal chain from interpersonal agent dissimilarities to dysfunctional buyer-supplier relations, culminating in interfirm pathological conflict. Moderating factors in the causal chain are: agent identity differentiation (for interpersonal dissimilarity), supplier relations mismanagement (for buyer-supplier relationship quality), and interfirm opportunism (for interfirm pathological conflict). Buyer-supplier interfirm incompatibility mediates the causal link between interpersonal dissimilarity and buyer-supplier relationship quality. Identity differentiation, the validation of one's self-image, is introduced as a process that determines buyer-supplier agent interpersonal dissimilarity judgments. This framework uses a contextual perspective. It describes interactions between observations of micro-level phenomena of interpersonal dissimilarities and macro-level models of interfirm fit. From a managerial perspective, interpersonal relations between individual buyer and supplier agents may be further strengthened by such strategies as expanding the scope of the interpersonal relationship, relaxation of role responsibilities, and volunteering business-related contact referrals.Originality/value: A new theoretical framework has been devised to predict and explain relationship quality and interfirm pathological conflict in the business-to-business context. The framework contributes to the value of the knowledge base by serving as a means for building new diagnostic tools for assessment of interfirm behavioral issues affecting exchanges. New concepts are introduced to enhance current literature on business-to-business marketing. The framework provides concreteindicators that operationally define ideas and enable or improve measurement for empirical modeling.
Keywords: business marketing; dept.mkt; industrial marketing; relationship quality; similarity; supplier compatibility

Knowledge and skills transfer between MBA and workplace - Prince, Melvin; Burns, David J; Lu, Xinyi; Winsor, Robert D (Journal of Workplace Learning, 2015)
Purpose-This paper aims to use goal-setting theory to explain the transfer of knowledge and skills between master of business administration (MBA) and the workplace. Design/methodology/approach-Data were obtained by an online survey of MBA students enrolled in at four US graduate business schools. These were a public and private institution in the Northeast region, a private sectarian institution in the Midwest region and a private institution in the Pacific region. All students worked while attending the university. The sampling frame consisted of each school’s MBA enrollees. Questionnaires were distributed to a random cross-section of part-time students at each graduate school of business representative of returned by 144 students. The profiles of responders were consistent with parameters for the entire MBA student population. Findings-The research shows that multiple goals of reciprocal knowledge and skills transfer may be in harmony and mutually reinforcing. In principle, each goal is more likely to be attained with greater economy of effort than might be surmised. Additionally, the same forces may act similarly to facilitate attainment of two well-integrated goals, in this case transfer betweenMBAstudies and work, as well as between work and MBA studies. Research limitations/implications-The present study involved participants from part-time public and private MBA granting institutions in the USA. The study tested and extended goal-setting theory and introduced the innovative concept of reciprocal transfer. Future studies should seek to generalize the findings to a broader population of part-time MBA students, especially from other nations. Despite its strengths, the findings of this study need to be interpreted in the perspective of some limitations. The current study did not measure transfer climates in either the organization or university settings. Transfer climates undoubtedly have an important bearing on transfer outcomes. Practical implications-Review of the present study suggests that a positive MBA environment is needed to influence motivation to learn and perceptions of the MBA program’s utility, thereby promoting transfer of knowledge and skills to MBA studies from the workplace. A supportive work-to-MBA-studies transfer climate will lead to more active learning of course content that has greater relevance for achieving career goals. Potentially generalizable from the organizational transfer climate literature (Rouiller and Goldstein 1990; Rouiller and Goldstein 1993), positive transfer from work to MBA studies will occur when appropriate situational cues and consequences are present in the program. Social implications-A constructive implication suggested by the findings of this study would be the intervention and transfer management by educators to structure and strengthen the university transfer climate of their part-time MBA programs. Traditionally, the concept of transfer climate has been primarily applied to employee workplace training activity and job performance. The university culture of the MBA student might emphasize and reward continuous learning from workplace experiences. Opportunities at the university should be provided for the exercise of newly acquired workplace skills that reinforce MBA learning experiences. Originality/value-This is the first study that shows how learning goals and performance goals are integrated in the context of a new concept, i.e. reciprocal transfer of knowledge and skills betweenMBA and workplace settings. It also demonstrates, for the first time, the impact of learning and motivation for MBAstudies and perceived utility ofMBAprogram on the extent of transfer of learning and skills from the workplace to the university setting. © Emerald Group Publishing Limited.
Keywords: Knowledge transfer; Learning orientation; Management education; Performance; dept.mkt

The effects of part-time MBA programs on students: the relationships between students and their employers - Prince, Melvin; Burns, David J; Manolis, Chris (The Journal of Education for Business, 2014)
The authors explore how the relationship between part-time master of business administration (MBA) students and their employers changes as students proceed through their MBA program by examining the degree to which students are integrated into their employer organizations. Significant positive relationships observed between students’ progress through their MBA program and the integration factors of coworker support and future prospects with their employers suggest that an MBA education can have a positive effect on employee–employer integration levels. Consequently, in addition to increasing business knowledge and skills, an MBA degree appears to assist with integrating employees and employers. © 2014, Copyright © Taylor & Francis Group, LLC.
Keywords: MBA education; coworker support; dept.mkt; graduate education; part-time MBA students; training

Use of comforting to enhance social marketing success A case study - Forbus, Robert; Snyder, Jason L (Social Marketing Quarterly, 2013)
Successful behavioral change is the Holy Grail for social marketers. Meta-analysis demonstrates that effect sizes of behavioral change in social marketing campaigns is typically low. The present case study uses 4 years of survey data from an Alabama weight loss and behavioral change campaign to develop an explanation for why some people are more successful in lifestyle change efforts than others. Comforting, a communicative form of prosocial behavior, produced the greatest magnitude of change when tested as an independent variable on dependent variables, including pounds lost, amount of dairy products and water consumed, and physical activities undertaken. The case study concludes by discussing implications for social marketing academics and practitioners. © The Author(s) 2013.
Keywords: Behavioral change; Comforting; Social marketing campaigns; Social support; Weight loss; dept.mkt

Attendance policies, student attendance, and instructor verbal aggressiveness - Snyder, Jason L; Forbus, Robert; Cistulli, Mark D (The Journal of Education for Business, 2012)
The authors utilized an experimental design across six sections of a managerial communications course (N = 173) to test the impact of instructor verbal aggressiveness and class attendance policies on student class attendance. The experimental group received a policy based on the principle of social proof (R. B. Cialdini, 2001), which indicated that for similar students, class attendance was linked to high academic performance. Students also assessed their instructor's level of verbal aggressiveness (D. A. Infante, 1979). Results suggest that instructor verbal aggressiveness did not influence class attendance. However, social proof did positively influence class attendance rates under certain circumstances. The authors discuss the study implications. © 2012, Copyright Taylor & Francis Group, LLC.
Keywords: attendance; dept.mkt; policy; social proof; verbal aggressiveness

A model of trust and compliance in franchise relationships - Davies, Mark A. P.; Lassar, Walfried; Manolis, Chris; Prince, Melvin; Winsor, Robert D. (Journal of Business Venturing, 2011)
Despite the danger of franchisee non-compliance as a severe impediment to overall franchise operation and performance, there is currently minimal understanding of the key factors that lead to these behaviors. Using a foundation of relational exchange theory, we construct and test a model that demonstrates how two distinct forms of trust, based upon perceptions of franchisor integrity and franchisor competence, are critical to explaining the roles that relational conflict and satisfaction play in influencing franchisee compliance. Implications of these findings are then demonstrated to have compelling relevance to the effective management of franchise systems. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Compliance; Conflict; Franchising; Reciprocity; Satisfaction; Trust; dept.mkt

Switching costs and ad agency-client relationship longevity: an exploratory study - Davies, Mark; Prince, Melvin (Services Marketing Quarterly, 2011)
A model of switching costs is applied to ad agency-client relationships using agency theory. Switching costs are comprised of set-up costs that create barriers to switching to new agencies and exit costs that are barriers to severing relationships with current agencies. Switching cost theory offers insights into why large clients can maintain agency relationships. A survey of American clients shows how client size is associated with set-up and exit costs. These relationships are explained through diversity and scope of services, the creative risk associated with major brands, and the need for more sophisticated monitoring, each acting as switching barriers, extending longevity. © Taylor & Francis Group, LLC.
Keywords: Account longevity; Client size; Switching costs; dept.mkt

Social Interaction and Employee Health - Forbus, Robert; Snyder, Jason (Journal of Business Management and Change, 2011)
With social interaction, quantity does not equal quality. Persons may have frequent negative social interactions with other persons, such that the interactions are socially undermining, rather than socially supportive. Rook (1984) used regression analysis to demonstrate how negative social interactions impact upon well-being outcomes more powerfully and more consistently than do positive social interactions. Building upon Rook’s work, the present research examines a workplace weight loss intervention and demonstrates the power of socially supportive communication in measures of weight loss and healthy lifestyle changes. Management implications are discussed.
Keywords: Social interaction; dept.mkt; employee health; weight-loss interventions; ⛔ No DOI found

Virtual identities from virtual environments - Prince, Melvin (Handbook of Research on Digital Media and Advertising: User Generated Content Consumption, 2011)
The creation of identities in immersive online digital environments has become commonplace in consumer behavior. Consumers frequently enter into socially networked, computer mediated environments (CME’s) as avatars. A user can design his or her avatar by choosing typologies of facial features, body types and clothing styles. The chapter concerns Avatar analysis as a system for generating and analyzing consumer information of practical value to marketers. Avatar analysis enhances understanding of brand perceptions and meanings, discovers new ways of positioning and differentiating brands, and provides insights for improving the effectiveness of brand communications. Using websites such as Second Life to draw avatars, consumer identity projections are elicited based on consumers’ perceptions and interpretations of their own digital figure drawings i.e., virtual social identities of consumers and brands. These identity projections disclose their real and ideal selves, brand-as-a-person, and imagery of a typical brand user.
Keywords: dept.mkt

Advertising agency compensation, client evaluation and switching costs: an extension of agency theory - Davies, Mark; Prince, Melvin (Journal of Current Issues and Research in Advertising, 2010)
We develop a theory of advertising agency compensation, client evaluation and switching costs, with extensions to agency theory. When clients are exposed to high switching costs, they become more vulnerable to the risk of agency costs. In response, clients can select compensation and evaluation decisions that convey fairness, signal their commitment, and invite agency reciprocity. With high switching costs, outcome-based compensation and formal evaluation procedures are likely. High switching costs are associated with signifi'cant relationship investments, mature relationships, large clients, formal evaluation, and with clients that use their agencies as strategic partners. Clients surveyed in North America support the theory. © 2010 Taylor and Francis Group, LLC.
Keywords: dept.mkt

A study of marketing standardization and performance of australian, japanese, and U.S. firms - Kustin, Richard Alan (Journal of Asia-pacific Business, 2010)
Given the continued importance of the globalization era, there is an ever-increasing interest in the correlation between marketing mix standardization and the firm's market performance. This issue focuses on the firm's pursuit of global markets in an environment conditional to internal and external market factors. The research examines factors on multinational firm's marketing mix (program and process marketing) from Australia, Japan, and the United States and the impact on market performance. The results are mixed providing some support for marketing standardization and profit performance. © Taylor & Francis Group, LLC.
Keywords: Australia; Global Marketing; Japan; Marketing Mix; Profit Performance; Standardization; Strategic Marketing; United States; corporate strategy; dept.mkt; globalization; marketing; multinational enterprise; standardization

Performance and standardization of Australian, Japanese and US firms - Kustin, Richard Alan (Asia Pacific Journal of Marketing and Logistics, 2010)
Purpose – Globalization has fostered greater interest in all aspects of standardization theory including the 4Ps of the marketing mix or program and process marketing. The purpose of this paper is to probe the question: “Is there a benefit to the firm's strategy of marketing standardization that correlates positively to the firm's profit?”. Design/methodology/approach – Multinational firms from Australia, Japan and the USA operating in a global environment were studied in order to correlate marketing standardization to profit performance. Several methods of analysis were used including regression and analysis of variance measures. Findings – The results indicate there is increasing support for a strategy of standardizing marketing mix components and contributing to a firm's profit performance. Originality/value – The paper adds to the current literature by providing further empirical research correlating marketing mix standardization to profit. © 2010, Emerald Group Publishing Limited
Keywords: Australia; Globalization; Japan; Marketing strategy; Standardization; United States of America; dept.mkt

The earth is flat, almost: measuring marketing standardization and profit performance of japanese and U.S. firms - Kustin, Richard Alan (Journal of Global Marketing, 2010)
Globalization has fostered greater interest in all aspects of standardization theory, including the four Ps (product, price, place [distribution], and promotion) of the marketing mix. The study researches the firm's strategy of marketing standardization as it correlates to the firm's profit. Multinational firms from Japan and the United States operating in a global environment were studied in order to correlate marketing standardization to profit performance. The results indicate there is increasing support for a strategy of standardizing marketing mix components and contributing to a firm's profit performance. © Taylor & Francis Group, LLC.
Keywords: Global marketing; Global strategy; Globalization; Marketing standardization; Profit performance; dept.mkt

CEO archetype identity drives organization culture - Prince, Melvin; Forr, James; Wardlaw, Jim; Plummer, Joseph (Journal of Leadership Studies, 2019)
In the current study the relationships between CEO archetypes and organizational climate were examined. Archetypes are historical, mythical, and cultural representations that are shared in our collective unconscious. Data were collected from a CEO and his employees, using a mixed methods research approach which involved the Zaltman Metaphorical Elicitation Technique (ZMET), as well as personality measures and quantitative assessments of organizational climate. The CEO archetype as perceived by employees is that of a benevolent patriarch which mirrors the CEO's self-concept as caring for the well-being of employees. Employees ascribed the stress-free and nurturing organizational climate to the CEO's archetypical leadership style. However, their organizational climate, in principle, leads to excessive employee familistic dependence on the CEO for making important organizational decisions and supplying creative ideation. The present study of a CEO archetype and its bearing on organizational climate is unique, filling an important gap in management knowledge. Implications of the study involve the channeling of its insights about the archetype-embedded organizational climate, so as to better select administrative managers, improve organizational communication trust and openness, stimulate creative innovation, handle organizational crises, and generally promote employee well-being. © 2019 University of Phoenix
Keywords: dept.mkt; peer-reviewed

The moral bases of consumer ethnocentrism and consumer cosmopolitanism as purchase dispositions - Prince, Melvin; Yaprak, Attila N.; Palihawadana, Dayananda (Journal of Consumer Marketing, 2019)
Purpose: This paper aims to develop a model that explains the moral bases of consumer ethnocentrism and consumer cosmopolitanism as purchase dispositions. The authors build their work on moral foundations theory and the social theories of Emile Durkheim. Design/methodology/approach: Theory-building from general theories of motivation is grounded in cultural norms, and empirical research is conducted to test theoretical propositions. Findings: The focus is on the theoretical implications of binding or individualism morals of consumers within social groups. Consequently, variables in the model relate to ethical themes of community, autonomy and divinity. This theory posits that, for a variety of considerations, loyalty has a direct and positive effect on consumer ethnocentrism and on consumer cosmopolitanism. Serendipitously, other moral foundations have negative effects. The authors theorize that negative relationships exist between authority and consumer cosmopolitanism, and between sanctity and consumer ethnocentrism. This model also illustrates that consumer ethnocentrism positively predisposes favorable domestic product judgments. Research limitations/implications: New ethical factors in consumer dispositions affecting product purchase decisions are explored. Hypotheses can be empirically replicated and moderated in future research. Practical implications: Marketers can use the variables of personal values, moral foundations and gender role identity to fashion marketing communications and to target selective consumer segments. Social implications: The persuasion process of social marketing will be enhanced by understanding relevant motives. Originality/value: The use of the fine-grained moral foundation antecedents to predict consumer predispositions of ethnocentrism and cosmopolitanism is without precedent. © 2019, Emerald Publishing Limited.
Keywords: Consumer ethics; Consumer ethnocentrism; Consumer psychology; dept.mkt; peer-reviewed

Consumer morality and moral consumption behavior: literature domains, current contributions, and future research questions - Yaprak, Attila; Prince, Melvin (Journal of Consumer Marketing, 2019)
Purpose: The literature on consumer morality and consumption is spread widely across many research streams and would benefit from grouping under selected themes so that scholars’ work can be guided by the compass of these themes. It is also important to add studies to each of these themes to serve as gateways that will guide new research. The aim of this special issue of the Journal of Consumer Marketing was to achieve precisely this purpose. The purpose of this paper is to open the gate to the exploration of the themes that today describe this landscape. Design/methodology/approach: The paper assesses the contributions made in each of several domains to better understand, why and how moral consumption works, what its ingredients are and how it may grow in the future. There are at least four domains of morality and moral consumption studies as follows: the formation of the moral self and moral identity; moral identity and ethical consumption; moral reasoning (cognitive processes) and moral choice; and the moral self and marketing. Each of these domains of work provides insight into the moral consumption phenomenon. Findings: The authors highlight the development of the moral self and underscore the significance of the relationship between identity development and the individual’s moral actions and by extension the significance of that relationship in moral consumption. Also, the paper adds to the current discussion on morality and ethical consumption by underscoring their interlinked nature and how that linkage can drive consumption behavior, highlight the cognitive processes involved in moral choices and how consumers reason to arrive at those choices. Finally, the authors provide examples of the workings of moral identity and reasoning in consumption contexts more directly. Originality/value: Each of these morality and moral consumption domains of work provides unique insights into the moral consumption phenomenon; thus, it is important to disseminate the contributions made in each domain to better understand, why and how moral consumption works, what its ingredients are and how it may grow in the future. In this paper, the authors offer contemporary original samples of key contributions to each of these domains. © 2019, Emerald Publishing Limited.
Keywords: Consumer morality; Ethical consumption; Moral choice; Moral consumption; Moral identity; Moral reasoning; dept.mkt; peer-reviewed

Political economy of farm loan waivers in India - Jha, Srirang; Mohapatra, Amiya Kumar; Lodha, Shyam S. (FIIB Business Review, 2019)
Political leadership of various states in India is under tremendous pressure to provide instant relief to the farmers reeling under debt trap, resulting in suicides in several cases. Often, suicides by peasants are widely covered in the media which in turn sway the people’s perception about apparent indifference of the government towards the farming communities of the country. This certainly brings in concerns related to political economy revolving around judicious distribution of wealth and national income of the country. State governments of India are generally reluctant to waive off the farm loans as a matter of routine due to concomitant burden on exchequer that might adversely affect their fiscal balances. However, political parties tend to use farm loan waiver as tactics to come to power in spite of the fact that such populist measures are not good for the economy, nor do they offer a long-term solution to the age-old problem of higher degree of incidence of indebtedness among the farming communities. This article explores the antecedents and consequences of farm loan waivers and the way forward. Besides, it also reconnoitres whether the state takes such decisions as farm loan waiver purely on the basis of economics or any hidden political agenda.
Keywords: dept.mkt; peer-reviewed

The Diogenes Effect in retail buyer information processing - Prince, Melvin; Kwak, Lynn; Priporas, Constantinos Vasilios (Journal of Retailing and Consumer Services, 2019)
The search for an ethical vendor who is honest and trustworthy in the exchange process is conceptualized as the Diogenes Effect, an innovative concept. In the light of this effect, the theoretical framework of the current study's model involved retail buyer responses to vendor persuasive communications. The model was tested by having a sample of retailer buyers complete a survey of information processing in the search for a product and vendor. This study innovatively links vendor communication effects to retailer buyer decision-making and evaluations by incorporating and integrating elements of Elaboration Likelihood Theory. Contributing to theory-building, it was found that when retailer buyers searched for a vendor with an ethical orientation, the result was intensified central processing of information and decreased peripheral information processing. This was especially salient when retailer buyers had greater longevity of professional experience. The next stage, information processing, led to feedback that enabled assessment of vendor trustworthiness. Finally, the research measured the level of fulfillment in the post-purchase phase. In the end, typical outcomes included the generation of favorable expectations of vendor performance, as well as the positive impact of those heightened favorable expectations on greater satisfaction with the value ultimately received from the vendor.
Keywords: Diogenes; Diogenes effect; Elaboration likelihood model; Expectations; Information processing; Retailer buying decision; Satisfaction; decision making; dept.mkt; information processing; modeling; peer-reviewed; retailing

Mindful consumption: Three consumer segment views - Milne, George R.; Ordenes, Francisco Villarroel; Kaplan, Begum (Australasian Marketing Journal, 2020)
As consumers are moving away from mindless consumerism, a mindful consumption literature has emerged that is based on Buddhist and psychological perspectives of mindfulness. While the idea of mindful consumption has great potential, there is little empirical research to date that comprehensively examines the consumer perspective on the role of mindfulness on consumption. To provide a grounded consumer perspective, the authors segment mindful consumption views from open-end text using a mixed method of clustering and text mining. By analyzing the segmentation structure, the authors discover various consumer views of mindful consumption, such as careful economic based consumption, monitoring activities of firms, and being informed about the impact of consumption choices. The authors compare the empirical results with the academic literature to provide directions for future research. © 2019 Australian and New Zealand Marketing Academy
Keywords: Mindful consumption; Mindfulness; Segmentation; Sustainability; Text mining; dept.mkt; peer-reviewed

Uniting theory and empirical research: market sensing and marketing research - Prince, Melvin; Gabay, G; Priporas, Constantinos; Moskowitz, H (Quantitative research methods in consumer psychology: contemporary and data driven approaches, 2018)
Quantitative consumer research has long been the backbone of consumer psychology producing insights with peerless validity and reliability. This new book addresses a broad range of approaches to consumer psychology research along with developments in quantitative consumer research. Experts in their respective fields offer a perspective into this rapidly changing discipline of quantitative consumer research. The book focuses on new techniques as well as adaptations of traditional approaches and addresses ethics that relate to contemporary research approaches. The text is appropriate for use with university students at all academic levels. Each chapter provides both a theoretical grounding in its topic area and offers applied examples of the use of the approach in consumer settings. Exercises are provided at the end of each chapter to test student learning. Topics covered are quantitative research techniques, measurement theory and psychological scaling, mapping sentences for planning and managing research, using qualitative research to elucidate quantitative research findings, big data and its visualization, extracting insights from online data, modeling the consumer, social media and digital market analysis, connectionist modeling of consumer choice, market sensing and marketing research, preparing data for analysis;, and ethics. The book may be used on its own as a textbook and may also be used as a supplementary text in quantitative research courses.
Keywords: dept.mkt

We beat the cops in GTA: Po(ludic)al activism in the age of video games - Demirbag-Kaplan, Melike; Kaplan-Oz, Begum (Convergence, 2018)
This article explores how individuals reflect on their digital experiences of actualizing fantasies to make sense of their everyday actions, particularly in the context of video gaming. Our study takes a qualitative approach to understanding the context of materializing consumer fantasies, as initially experienced and actualized in video games, and how these fantasies are transformed into material reality, through an investigation of an illustrative case of mass street protests, the 2013 Gezi Protests in Turkey. The findings suggest that digital virtual experiences in video games have obvious manifestations in the material world, as consumers travel on the borders of reality, moving back and forth into the liminoid terrain of the digital virtual, and provide a deeper understanding of how the blurred boundaries between the virtual and material are established in practice.
Keywords: Digital virtual consumption; Gezi Protests; dept.mkt; liminoid; peer-reviewed; political activism; social movements; video games

Coffee with co-workers: role of caffeine on evaluations of the self and others in group settings - Unnava, Vasu; Singh, Amit Surendra; Unnava, H Rao (Journal of Psychopharmacology, 2018)
This research explores the effect of consuming a moderate amount of commercially available caffeinated coffee on an individual’s self-evaluated participation in a group activity and subsequent evaluations of the experience. Across two studies, results show that consuming a moderate amount of caffeinated coffee prior to indulging in a group activity enhances an individual’s task-relevant participation in the group activity. In addition, subjective evaluations of the participation of other group members and oneself are also positively influenced. Finally, the positive impact of consuming a moderate amount of caffeinated coffee on the evaluation of participation of other group members and oneself is moderated by a sense of an increased level of alertness.
Keywords: Caffeine; coffee; dept.mkt; group discussion; peer-reviewed

When nostalgia marketing backfires: Gender differences in the impact of nostalgia on youthfulness for older consumers - Kim, Young Kyu; Yim, Mark Yi-Cheon (Applied Cognitive Psychology, 2018)
Two studies are conducted to test how consumers respond differently in feeling nostalgic depending on age and gender. Study 1 uses narrative writing tasks to empirically test the effect of nostalgic versus nonnostalgic feelings on youthfulness by age and gender. To increase the external validity of our findings in Study 1, Study 2 replicates it using print ads. The results across the two studies consistently reveal a significant effect of nostalgia on feelings of youthfulness that differs by age and gender. Specifically, older women tend to feel less youthful than older men when nostalgic feelings are induced in both studies, whereas younger adults experience no gender difference. Results also show that these differences are explained by self-discontinuity between current and ideal body image. Furthermore, we identify that nostalgic feelings in advertising are effective because they generate positive feelings of youthfulness that in turn result in positive attitudes toward the ad.
Keywords: adult; advertising; age; article; body image; consumer; dept.mkt; female; gender; human; human experiment; male; marketing; nostalgia; peer-reviewed; self-discontinuity; sex difference; youthfulness

Using intuitive awakening for business students to enhance strategic thinking skills - Prince, Melvin; Priporas, Constantinos (Australasian Marketing Journal (AMJ), 2018)
Keywords: dept.mkt; peer-reviewed

Relational communication and illusionary loyalty: Moderating role of self-construal - Hossain, Mehdi T; Chonko, Lawrence B (Industrial Marketing Management, 2018)
In this research we demonstrate how various facets of communication influence customer loyalty in a B2B selling environment. Palmatier, Scheer, and Steenkamp (2007) show that salesperson owned loyalty (customers' loyalty specific to the salesperson) can be differentiated from customers' overall loyalty to the firm. We demonstrate how various facets of communication differentially influence salesperson owned loyalty and loyalty to the firm. We find that greater bidirectional flow of communication enhances both salesperson owned loyalty and customers' loyalty to firm. However, greater frequency of communication enhances only salesperson owned loyalty. Formality in communication negatively influences salesperson owned loyalty and positively influence customers' loyalty to firm. In addition, we find an interesting moderation effect of these relationships by customers' self-construal. Theoretical and practical implications of our findings are discussed.
Keywords: Communication facets; Loyalty to firm; Relationship marketing; Salesperson owned loyalty; Self construal; dept.mkt; peer-reviewed